Proposal of using sensor networks for measurements of the efficiencies of a low cost vertical wind turbine - Penereiro, Júlio César; Araujo, Guilherme de Souza (Acta Scientiarum. Technology, 2018)
This work presents a vertical wind turbine with wind collector designed using low-cost materials and specific sensors for the acquisition of physical quantities relevant to obtain measures of efficiencies under different conditions of use. We describe the selection of materials; construction, assembly and mechanical tests and, mainly, sensors with applications of electrical and electronic elements; as well as some tests made to obtain the instantaneous and average efficiencies. We decided to perform experimental measurements by means of digital temperature sensors, speed of rotation, voltimeters and amperimeters, which were placed at strategic points of the wind power device. Simultaneously, using an anemometer, sought to make wind speed measurements in some experimental tests. So, it was necessary to build and refine traditional microcontroller boards whose functions were to identify and read all measurements, in addition to performing the interface between the sensors employed with the microcomputer used. The experimental parameters were identified with programs using the ScadaBR and Excel, specifically developed as necessary. Â